Personalized Management Of Gastric Cancer In The Era Of Molecular Profiling (Eurasian Research Bulletin, 2026)
This article presents a pragmatic, biomarker-centered framework for tailoring gastric cancer management in an era where molecular profiling increasingly drives everyday clinical decisions. Although stage and histopathology still define the baseline strategy, treatment selection in real practice now depends on a small group of predictive markers that inform perioperative choices, first-line therapy for metastatic disease, and the sequencing of later lines. The review concentrates on biomarkers with immediate clinical utility that routinely shape care: HER2 status, PD-L1 combined positive score, mismatch repair deficiency or microsatellite instability, and CLDN18.2 expression. It synthesizes the evidence behind key treatment “pivot points,” including perioperative FLOT in resectable disease, integration of PD-1 blockade with chemotherapy for HER2-negative metastatic tumors with PD-L1 CPS guiding expectations of benefit, incorporation of pembrolizumab into trastuzumab-plus-chemotherapy backbones for HER2-positive disease, use of trastuzumab deruxtecan after failure of trastuzumab-based regimens, and first-line zolbetuximab-based combinations for CLDN18.2-positive cancers. An actionable testing-and-treatment pathway is proposed, alongside real-world challenges that can undermine implementation, such as assay-to-assay variability, intratumoral heterogeneity, and the clinical value of re-evaluation at progression in selected patients. The central conclusion is straightforward: molecular profiling has moved beyond an academic exercise and now functions as the main control mechanism guiding modern gastric cancer therapy.